Nursing care in newborn pain relief: integrative review - Farias, Leiliane Martins; Rêgo, Rita Maria Viana; Lima, Francisca Elisângela Teixeira; Araújo, Thelma Leite de; Cardoso, Maria Vera Lúcia Moreira Leitão; Souza, Ângela Maria Alves e (Rev Rene, 2011)
This is a bibliographic research that aimed to identify in nursing publications the non-pharmacological actions used in pain relief of newborns. The survey was carried out in May 2010, with the descriptors “Pain”, “Infant, Newborn” and “Nursing”, in LILACS, PubMed, CINAHL and SCOPUS databases. 12 articles were selected, and we could identify as non-pharmacological measures of pain relief: glucose pacifier at 25%, non-nutritive sucking, change of position, massages, kangaroo position, mother’s scent, music therapy, parents’ presence and images for amusement. It was inferred that non-pharmacological measures can relieve the pain of newborns and their use in nursing practice provides favorable results to reduce the pain of newborns, therefore it is suggested the elaboration of experimental researches to base and support the practice based on evidences.